Seismic Tomography and Earthquake Relocation in North China Craton From 2008 to 2017 - Wu, Bateer; Ma, Tian (Frontiers in Earth Science, 2022)
In this paper，we present a joint inversion investigation of both 3-D P-wave velocity structure and hypocenter parameters using double-difference seismic tomography method in North China Craton．The double-difference seismic tomography method was adopted to refine the absolute and relative event locations and 3-D P-wave velocity structures simultaneously with the direct use of both absolute arrival times．These data came from the earthquake catalog records of totally 18388 events recorded by 209 stations from the Beijing-Tianjin-Hebei Digital Seismic Network of China from 2008 to 2017.The inversion results indicated that this method produced a more pronounced and detailed velocity model of the North China Craton. which was more consistent with the features of the local geological setting．It revealed that in the orogenic belt or uplift area, the 3-D P-wave velocity structure is a high-speed anomaly zone, while in the depression zone, the 3-D P-wave velocity structure is a low-speed anomaly zone. The structure of 3-D P-wave velocity in the study area is discontinuous and there are many abnormal bodies. The inverted 3-D P-wave velocity structure in shows that the velocity is not completely continuous in both horizontal and vertical directions, and there are many abnormal velocity regions. Horizontal discontinuity is due to the interaction between uplifts and depressions in North China. Vertical discontinuity is due to the upwelling of magma caused by plate movement and the decrease of velocity caused by rock melting. At the same time, after the earthquake relocation, we find that the earthquakes are concentrated near the fault zone, and most of them occur at the depth of 0-20 km.